Worldwide research productivity in the field of psychiatry - Zhang, Jinghua (Int J Ment Health Syst, 2017)
BACKGROUND: The field of psychiatry has seen significant progress in recent years due to worldwide contributions. National productivity, however, in the field of psychiatry is still unclear. In our study, we investigated contributions of individual nations to the field of psychiatry. METHODS: The Web of Science was used to perform a search from 2011 to 2015 on the subject category “psychiatry”. The total number of articles, citations and the per capita numbers were obtained to analyze the contributions of different countries. RESULTS: In psychiatry journals from 2011 to 2015, 84,760 articles were published worldwide. The most productive world areas were North America, East Asia, Europe and Oceania. The percentage of articles published in high-income countries was 87.77%, middle-income countries published 12.07%, and lower-income published 0.16%. Most articles were published by the United States (32.68%); the United Kingdom was next (8.59%), which was followed by Germany (6.77%), Australia (5.87%), and Canada (4.9%). The country with the highest number of citations (243,394) was the United States. A positive correlation was found between the population/GDP and the number of publications (P < 0.01). Australia ranked the highest when normalized to population size, and the Netherlands and Norway were next. The Netherlands ranked highest, followed by Israel and Australia when adjusted for GDP. CONCLUSIONS: The authorship of most of the psychiatry articles was from high-income countries and few papers came from low-income countries. The most productive country was the United States. However, when normalized to population size and GDP, some European and Oceania countries were most productive. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13033-017-0127-5) contains supplementary material, which is available to authorized users.